Anti‐Inflammatory/Antioxidant Features of Adipose Tissue Mesenchymal Stem Cells Conditioned Media for Doped TiO2 Nanoparticles in Induced Inflammation - Ahmed A. Abd‐Rabou; Ahmed M. Youssef; Mohamed I. El‐Khonezy; Soheir E. Kotob; Mohamed S. Kishta (ChemistryOpen)
The fundamental purpose of this work is to determine the anti‐inflammatory/antioxidant activity of stem cell conditioned medium enhanced by mono‐ or dual‐doped TiO2 nanoparticles. The transmission electron microscope, X‐ray diffraction, and energy‐dispersive X‐ray analyses are used to characterize the nanoparticles. Isolation/characterization of adipose tissue mesenchymal stem cells (AD‐MSCs) is done. In vitro assays reveal that protein denaturation and proteinase induction are significantly increased with lipopolysaccharide (LPS) comparable to control, while treatments significantly decrease the induction compared to LPS. In vitro assays reveal decreasing in hydroxyl radical scavenging and DPPH radical scavenging activities with LPS, while treatments significantly increase the activity compared to LPS. Induction with LPS decreases in vitro catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) expression levels and enzyme activities are significantly compared to controls, while treatments significantly increase the CAT expression compared to LPS. Induction with LPS increases the in vitro interleukin 4 (IL4), IL6, IL10, and tumor necrosis factor α expression levels, and their activities significantly decline with treatment compared to controls, while treatments significantly decline expression compared to LPS. The anti‐inflammatory and antioxidant properties of AD‐MSC‐conditioned medium enhanced with mono‐ or dual‐doped TiO2 nanoparticles are identified in this investigation. To sum up, the work has shown that mono‐ and dual‐doped TiO2 can inhibit the inflammation caused by LPS in vitro.